2020
DOI: 10.1002/ece3.7001
|View full text |Cite
|
Sign up to set email alerts
|

Picture worth a thousand words: Updating repeat photography for 21st century ecologists

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Repeat photography is the practice of replicating pre‐existing photographs for documenting and quantifying changes over time (Depauw et al., 2022; Hammond et al., 2020). It allows us to document habitat restoration and ecosystem changes in an oblique view, better aligning with how people perceive the world and thus offering a great tool for communication purposes.…”
Section: Drone Applications In Line With the Goals Of The Parkmentioning
confidence: 99%
“…Repeat photography is the practice of replicating pre‐existing photographs for documenting and quantifying changes over time (Depauw et al., 2022; Hammond et al., 2020). It allows us to document habitat restoration and ecosystem changes in an oblique view, better aligning with how people perceive the world and thus offering a great tool for communication purposes.…”
Section: Drone Applications In Line With the Goals Of The Parkmentioning
confidence: 99%
“…The use of photographs in the studies of landscape change allows the rapid documentation of spatial change, but in addition to the requirements for the angle and position of the photographs, it is difficult to analyse the spatial depth and other three-dimensional visual features. For example, Hammond et al found that the similarity of the photographs before and after two years was around 90% by calculating the similarity of the pictures after repeating the photographs at the same location in 2015, 2016, and 2017 [51]. Li showed by analysing the Google Street View images of New York City that the mean Green View Index of the study area increased from 19.33 to 19.77 from 2008-2013 to 2014-2018 [52].…”
Section: Confirming the Long-term Changes In Visual Attributes Of Urb...mentioning
confidence: 99%
“…It is a common method to analyse long‐term landscape, land‐use and vegetation changes from an ecological perspective (Nusser, 2000; Pickard, 2002; Santana‐Cordero & Szabo, 2019; Vellend et al, 2013). Repeat photos allow researchers to study the effect of anthropogenic and natural disturbances on a finer spatial resolution than is possible with satellite imagery (Hammond et al, 2020), and at time‐scales beyond those accessible by long‐term ecological monitoring (Hoffman et al, 2020). They allow to obtain insights in historical ecological conditions with limited resources.…”
Section: Three Promising Avenues For the Use Of Photos In Ecological ...mentioning
confidence: 99%
“…Repeat photography is also used on smaller time-scales compared to repeat historical photographs, when new timeseries are started by researchers who frequently (e.g. once a year) revisit the study site(s) Hammond et al, 2020). For instance, Hietz et al (2002) used repeated photographs of branches, taken once a year in summer, to monitor the growth and survival of epiphytes over a 5-year period.…”
Section: Repeat Photographymentioning
confidence: 99%